Housing Tribunals: Comparative Analysis of The Practices in Peninsular Malaysia, Sabah and Sarawak - Sufian, Azlinor (Universiti Malaysia Sarawak, 2012)
As a developing country, Malaysia can be proud of its structured mechanism in relation to land, housing and property. The mechanism will support the growth of these areas. This is also related to the confidence the public has in property developers. In Malaysia there are three housing tribunals that are applicable in three different jurisdictions, namely, the Tribunal for Homebuyers’ Claim in Peninsular Malaysia and the Tribunal for Housing Purchasers’ Claim in Sabah and Sarawak that came into force in 2002, 2007 and 2010, respectively. The purpose of the Tribunal is to minimise the burden that purchasers have to face in order to claim remedies from developers. It is the objective of this article to provide a comparative analysis of the provisions, rules and procedures of the Tribunal for Homebuyers’ Claim in Peninsular Malaysia and the Tribunals for Housing Purchasers’ Claim in Sabah and Sarawak. It is hoped that this comparison will yield improvements in the laws and regulations governing all three tribunals in Malaysia.